2018
DOI: 10.3389/fpsyg.2018.01980
|View full text |Cite
|
Sign up to set email alerts
|

Person-Environment Fit and Employee Creativity: The Moderating Role of Multicultural Experience

Abstract: Previous research has demonstrated the positive effects of congruent personal and environmental characteristics on creativity. None of them, however, has tested the formal theory of person-environment fit for predicting creativity in the context of multicultural experiences. This study examined the effects of two versions of person-environment fit (Demands-abilities fit and Needs-supplies fit) on employee creativity in China, taking into account the moderating role of multicultural experiences. The results, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 96 publications
(117 reference statements)
1
24
0
Order By: Relevance
“…Data were collected from the CGSS, which was a repeated cross-sectional survey in China. A detailed procedure about CGSS has been described previously [25,26]. Briefly, this survey has been conducted since 2003, using a multi-stage stratified probability proportionate to size sampling method to investigate Chinese adults (age ≥ 18).…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected from the CGSS, which was a repeated cross-sectional survey in China. A detailed procedure about CGSS has been described previously [25,26]. Briefly, this survey has been conducted since 2003, using a multi-stage stratified probability proportionate to size sampling method to investigate Chinese adults (age ≥ 18).…”
Section: Methodsmentioning
confidence: 99%
“…If employees feel their company attaches great importance to innovation, this will give them the belief that conducting innovative actions is encouraged; even if their innovation fails, they will not be punished, the subjective efforts of the employees will be stimulated and they will try innovative methods actively (Hommel et al, 2011). Conversely, if employees believe that the organization does not value innovation as they say, or that they will suffer big losses if they fail, then employees will be unlikely to try innovative and new processes or methods (Wang and Wang, 2018). Humorous leadership plays an important role in the creation of an organizational innovation atmosphere; in such an atmosphere, subordinates feel free to develop, communicate, and implement their ideas without any fear of negative consequences (Carmeli et al, 2010).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This example highlights how multicultural experiences and exposure to new cultures inspire new ideas. Multicultural experiences refer to all direct and indirect experiences of contact or interaction with elements and/or members of foreign cultures (Hu, Gu, Liu, & Huang, 2017); such experiences can facilitate the performance of individual creativity by improving individual enlightenment learning, distance imagination and concept formation and by generating novel ideas through unfamiliar culture (Wang & Wang, 2018). Under these circumstances, individuals draw new ideas from different cultures and integrate them in novel ways in problem-solving scenarios.…”
Section: The Influence Of Bilingual Learning and Willingness To Studymentioning
confidence: 99%
“…Under these circumstances, individuals draw new ideas from different cultures and integrate them in novel ways in problem-solving scenarios. Integrating seemingly unrelated concepts in different cultures helps to extend the conceptual category in the brain (Maddux, Adam, & Galinsky, 2010;Wang & Wang, 2018). summarized Maddux's and other scholars' studies (de Bloom, Ritter, Kühnel, Reinders, & Geurts, 2014;Fee & Gray, 2012;Maddux & Galinsky, 2009;Yi, Hu, Scheithauer, & Niu, 2013) and concluded that both long-term and short-term multicultural experiences can boost individual creativity and that improvement in cognitive fluency is among the most obvious outcomes.…”
Section: The Influence Of Bilingual Learning and Willingness To Studymentioning
confidence: 99%
See 1 more Smart Citation